Global research priorities for historical ecology to inform conservation - Mcclenachan, Loren; Rick, Torben; Thurstan, Ruth H.; Trant, Andrew; Alagona, Peter S.; Alleway, Heidi K.; Armstrong, Chelsey; Bliege Bird, Rebecca; Rubio-Cisneros, Nadia T.; Clavero, Miguel; Colonese, Andre C.; Cramer, Katie; et al. (My University, 2024)
Historical ecology draws on a broad range of information sources and methods to provide insight into ecological and social change, especially over the past similar to 12000 yr. While its results are often relevant to conservation and restoration, insights from its diverse disciplines, environments, and geographies have frequently remained siloed or underrepresented, restricting their full potential. Here, scholars and practitioners working in marine, freshwater, and terrestrial environments on 6 continents and various archipelagoes synthesize knowledge from the fields of history, anthropology, paleontology, and ecology with the goal of describing global research priorities for historical ecology to influence conservation. We used a structured decision-making process to identify and address questions in 4 key priority areas: (1) methods and concepts, (2) knowledge co-production and community engagement, (3) policy and management, and (4) climate change impacts. This work highlights the ways that historical ecology has developed and matured in its use of novel information sources, efforts to move beyond extractive research practices and toward knowledge co-production, and application to management challenges including climate change. We demonstrate the ways that this field has brought together researchers across disciplines, connected academics to practitioners, and engaged communities to create and apply knowledge of the past to address the challenges of our shared future.
Keywords: community engagement; knowledge co-production; ecological restoration; conservation policy; environmental management; climate change